PENERAPAN PENDIDIKAN AGAMA ISLAM DALAM LINGKUNGAN KELUARGA DI DESA KEBOAN KECAMATAN NGUSIKAN KABUPATEN JOMBANG - - Waslah (Universitas KH. A. Wahab Hasbullah, 2019)
In the effort to implement religious education at this time, it is necessary to introduce a strict understanding of religion to a child, so that children have good personalities that are in accordance with religion, all of which can be started by educating children at an early age through education and experience through with his family who acted as educators. Departing from this, then in this case what is raised is how the application of Islamic religious education in the family environment, how the level of adherence to the teachings of children's religion, obstacles encountered in the application of Islamic religious education in the family environment, and the efforts made by parents to deal with these obstacles in the village of Keboan, Ngarkan District, Jombang Regency. While the objectives to be achieved in this research are to find out and describe and protect the problems above. This study uses inductive and deductive methods, and the data collection uses interview, observation, questionnaire, and documentation methods, while the data analysis technique uses descriptive qualitative analysis supported by the use of percentage techniques, using the formula P = F / N x 100%, where P = percentage; F = frequency of each answer the respondent has chosen; and N = number of respondents. The results of the study in a nutshell show that the implementation of religious education in the children of Muslim families in Keboan Village, Ngusikan District, Jombang Regency as a whole can be said to be good. This can be proven in the application of Islamic religious education in the family environment, the level of adherence of children to religious teachings in the village of Keboan is of good value. And parents are aware of the inhibiting factors in the application of Islamic religious education in the family environment, as well as parents' efforts in overcoming these obstacles.